valtricotinevh
2022-07-26
Answered

If f(x)=x-2 and $g(x)=2{x}^{2}+3$, find(f+g)(x)

You can still ask an expert for help

Wayne Everett

Answered 2022-07-27
Author has **19** answers

$(f+g)(x)=f(x)+g(x)=x-2+2{x}^{2}+3=2{x}^{2}+x+1$.

asked 2021-09-10

A baseball team plays in a stadium that holds 55,000 spectators. With ticket prices at 10, the average attendance had been 27,000. When ticket prices were lowered to10,the average attend ance had been 27,000.When ticket prices were lowered to 8, the average attendance rose to 33,000. How should ticket prices be set to maximize revenue?

asked 2021-09-07

Whether each of these functions is a bijection from R to R.

a) $f(x)=-3x+4$

b) $f\left(x\right)=-3{x}^{2}+7$

c) $f(x)=\frac{x+1}{x+2}$

$d)f\left(x\right)={x}^{5}+1$

asked 2021-06-11

Find the linear approximation of the function

asked 2021-12-13

Find the general solution of the given differential equation

$x\frac{dy}{dx}-y={x}^{2}\mathrm{sin}x$

give the largest interval over which the genreral solution is defined.

give the largest interval over which the genreral solution is defined.

asked 2022-07-29

Evaluate the given function as required. Calculate C(0) and C(14) if C(t) is as shown below. Round your answers to decimal places $C(t)=1.5+2.75{e}^{-0.27}t$

asked 2020-11-23

The circle whose equation is $x\xb2+y\xb2=625$ is where the point E(-7, 24) is located. What is the sine of an angle when it is drawn in standard position and its terminal ray passes through E? .

(1) -7

(2) $-\frac{7}{24}$

(3) -24

(4) $-\frac{24}{25}$

asked 2022-10-27

Assume p is an even function and q is an odd function, given p,q lies on the entire real line, determine if $p\circ q$ is an even or odd function

Fundamentally,

Even function: $f(x)=f(-x)$

Odd function: $f(x)=-f(x)$

can I say that $p\circ q$ is an odd function because:

$(p\circ q)(x)=p(q(-x))=p(-q(x))=-(p\circ q)(x)$ ?

Fundamentally,

Even function: $f(x)=f(-x)$

Odd function: $f(x)=-f(x)$

can I say that $p\circ q$ is an odd function because:

$(p\circ q)(x)=p(q(-x))=p(-q(x))=-(p\circ q)(x)$ ?